A novel three dimensional samarium(III) coordination polymer with an unprecedented coordination mode of the 2, 5-pyridinedicarboxylic acid ligand: Hydrothermal synthesis, crystal structure and luminescence property. (9th March 2015) - Ay, Burak; Doğan, Nurhayat; Yildiz, Emel; Kani, İbrahim
Graphical abstract: A novel 3D coordination polymer was synthesized in a hydrothermal reaction. The thermal stability and photoluminescence properties of complex have been investigated. Abstract: A novel three dimensional (3D) coordination polymer [Sm(pic)2 (pydc)4 (H2 O)] n (pydc = pyridine-2, 5-dicarboxylate, Hpic = picolinic acid) (1 ) has been synthesized hydrothermally and characterized by elemental analysis, FT-IR, TG/DTA, single-crystal X-ray diffraction analysis and powder X-ray diffraction (PXRD). This compound crystallizes in the monoclinic space group P 21 / c with cell parameters a = 9.3041(13) Å, b = 14.216(2) Å, c = 10.5401(15) Å, V = 1387.72(30) Å 3 and Z = 4. Complex1 has a distinct 3D open-framework architecture due to the presence of picolinic ligands, which are converted from 2, 5-pydc ligands by in-situ decarboxylation under the hydrothermal conditions. The compound exhibits strong luminescent emissions because of the f-f transitions of the Sm(III) ion at room temperature. According to TGA/DTA analysis, the coordination polymer is thermally stable up to ∼300 °C.